Intraoperative assessment of transient and persistent regional left ventricular wall motion abnormalities in patients undergoing coronary revascularization surgery using real time three‐dimensional transesophageal echocardiography: A prospective observational study. Issue 11 (22nd August 2017) - Aggarwal, Neelam; Unnikrishnan, Koniparambil P.; Biswas, Indranil; Karunakaran, Jayakumar; Suneel, Puthuvasseri R.
Abstract : Objective: To evaluate the feasibility of intraoperative real time three‐dimensional echocardiography (RT3DE) for identification and quantification of transient and persistent regional wall motion abnormalities (RWMAs) in patients with ischemic cardiomyopathy undergoing coronary artery bypass grafting (CABG). Design: A prospective observational study Setting: Single‐center study in an academic tertiary care hospital Participants: A series of 42 patients undergoing elective CABG over a 2‐year period were included. Intervention: After induction of anesthesia, a comprehensive transesophageal echocardiography (TEE) examination was performed to evaluate regional wall motion using two‐dimensional wall motion score index (WMSI) and RT3D echocardiographic parameters at three specific time points during the operative phase. Measurements and main results: The 3D assessment of LV function was based on the quantification of change in LV chamber volume over time from each segment excursion. Patients were divided into two groups and subgroups based on TEE findings. There was significant mechanical dyssynchrony in patients with RWMAs (WMSI > 1; systolic dyssynchrony index [SDI] = 7.0 ± 3.66) as compared to the patients having normal wall motion (WMSI = 1; SDI = 2.0 ± 0.95; P = .001). Patients with contractile dysfunction were found to have low values of segmental excursion and high values of negative excursion on parametric imaging. Persistent RWMAs due to hibernating myocardium showed significant resolution of mechanical dyssynchrony after revascularization. Parametric imaging could detect transient RWMAs due to stunning and graft dysfunction. Early activating segments (EAS) on "timing bull's‐eye" may represent hypercontractile segments and may influence inotrope administration. Conclusion: The RT3DE is a valuable modality for precise quantification of regional wall motion during revascularization procedure.